2013
DOI: 10.1126/scitranslmed.3006070
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Imaging of Patients with Prostate Cancer Using Hyperpolarized [1- 13 C]Pyruvate

Abstract: This first-in-man imaging study evaluated the safety and feasibility of hyperpolarized [1-13C]pyruvate as an agent for noninvasively characterizing alterations in tumor metabolism for patients with prostate cancer. Imaging living systems with hyperpolarized agents can result in more than 10,000-fold enhancement in signal relative to conventional magnetic resonance (MR) imaging. When combined with the rapid acquisition of in vivo 13C MR data, it is possible to evaluate the distribution of agents such as [1-13C]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
1,552
3
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,151 publications
(1,585 citation statements)
references
References 38 publications
18
1,552
3
12
Order By: Relevance
“…The clinical potential of hyperpolarized MR is widely recognized, in particular in cancer research [63], and the first trial in patients using [1-13 C]pyruvate demonstrated that this technology can provide unique metabolic information for diagnostic purposes [64]. The foreseen applications in cardiac imaging and their expected impact in cardiology have been recently discussed [65][66][67].…”
Section: Resultsmentioning
confidence: 99%
“…The clinical potential of hyperpolarized MR is widely recognized, in particular in cancer research [63], and the first trial in patients using [1-13 C]pyruvate demonstrated that this technology can provide unique metabolic information for diagnostic purposes [64]. The foreseen applications in cardiac imaging and their expected impact in cardiology have been recently discussed [65][66][67].…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, our results demonstrate a potential for 13 C MRSI of HP [1-13 C]pyruvate as a neuroimaging method for assessment of inflammatory lesions. Because HP 13 C MRSI is clinically translatable (33) and expanding rapidly, this study is of high significance for future clinical trials not only on MS but also all neurological diseases presenting an inflammatory component (66). When used in conjunction with conventional MRI techniques, such a method would enhance diagnosis and help refine therapeutic regimens, which will ultimately improve clinical outcome and patient care.…”
Section: Discussionmentioning
confidence: 99%
“…These findings validate the potential of 13 C MRSI of hyperpolarized pyruvate for in vivo detection of neuroinflammation. cancerous lesions through the monitoring of the increased HP [1-13 C]pyruvate-to-lactate conversion, not only in preclinical cancer models but also in the clinical setting (33).…”
mentioning
confidence: 99%
“…17,[19][20][21][22] Furthermore, our group and others have recently demonstrated that MR measurement of [1-13 C]pyruvate and its metabolic intermediates can be performed in humans. 23,24 Translational work in pigs and rats has demonstrated that the use of hyperpolarized [2-13 C]pyruvate as a contrast agent can reveal 13 C signals from metabolites associated with the tricarboxylic acid (TCA) cycle. [1-13 C]Citrate has been observed directly, as has [5-13 C]glutamate, which is in exchange with the TCA cycle intermediate α-ketoglutarate (α-KG).…”
mentioning
confidence: 99%